Sport-Specific Morphology Profile: Differences in Anthropometric Characteristics among Elite Soccer and Handball Players - Marko Gusic; Stevo Popović; Slavko Molnar; Bojan Mašanović; Mica Radakovic (Montenegrin Sports Academy and Faculty for Sport and Physical Education, 2017)
The aim of this study was to obtain the relevant knowledge about significant differences in some anthropometric characteristics of top soccer and handball players. The sample included 41 male subjects divided into two subsamples. The first subsample included 25 subjects, who train in the senior selection in the Football club "Vojvodina" from Novi Sad, while the other subsample included 16 subjects who train in the senior selection in the Handball club "Vrbas" from Vrbas. The variables sample included 20 anthropometric measures that defined longitudinal and transversal dimensionality of skeleton, volume and mass of the body, and subcutaneous adipose tissue. The results were analysed in a statistical procedure marked as a significance testing of two arithmetic means of the independent samples, a t-test at the level of significance of p<0.05. It was concluded, based on these results, that significant differences occur in all variables for evaluation of subcutaneous adipose tissue, except for the skinfold of the upper arm and forearm, and in variables for evaluation of body height, body mass, the minimum circumference of the upper arm and lower leg, and the maximum circumference of the upper arm, forearm, upper leg and lower leg.